Socioeconomic Status and Access to Healthcare: Interrelated Drivers for Healthy Aging - McMaughan, Darcy Jones; Oloruntoba, Oluyomi; Smith, Matthew Lee (Frontiers in Public Health, 2020)
The rapid growth of the global aging population has raised attention to the health and healthcare needs of older adults. The purpose of this mini-review is to: 1) elucidate the complex factors affecting the relationship between chronological age, socio-economic status (SES), access to care, and healthy aging using a SES-focused framework; 2) present examples of interventions from across the globe; and 3) offer recommendations for research-guided action to remediate the trend of older age being associated with lower SES, lack of access to care, and poorer health outcomes. Evidence supports a relationship between SES and healthcare access as well as healthcare access and health outcomes for older adults. Because financial resources are proportional to health status, efforts are needed to support older adults and the burdened healthcare system with financial resources. This can be most effective with grassroots approaches and interventions to improve SES among older adults and through data-driven policy and systems change.